Formation mechanism of organo-chromium (III) complexes from bioreduction of chromium (VI) by Aeromonas hydrophila. (August 2019) - Huang, Xue-Na; Min, Di; Liu, Dong-Feng; Cheng, Lei; Qian, Chen; Li, Wen-Wei; Yu, Han-Qing
Abstract: Chromium is a common heavy metal widely present in aquatic environments. Cost-effective remediation of chromium-contaminated environment can be realized by microbial reduction of Cr(VI) to Cr(III). The genus Aeromonas species is one of such Cr(VI) reducers, whose reduction mechanism remains unrevealed and the main factors governing the Cr(VI) reduction pathways are unknown yet. In this work, the performances and mechanisms of Cr(VI) anaerobic reduction by Aeromonas hydrophila ATCC 7966 were investigated. This strain exhibited excellent Cr(VI) resistance and could utilize a suite of electron donors to support Cr(VI) bioreduction. The Cr(VI) bioreduction processes involved both extracellular (the metal-reducing and respiratory pathway) and intracellular reaction pathways. Adding anthraquinone-2, 6-disulfonate or humic acid as a mediator substantially enhanced the Cr(VI) bioreduction. The forms and distribution of the Cr(VI) bioreduction products were affected by the medium composition. Soluble organo-Cr(III) complexes were identified as the main Cr(VI) reduction products when basal salts medium was adopted. Given the environmental ubiquity of the genus Aeromonas, the findings in this work may facilitate a better understanding about the transformation behaviors and fates of Cr(VI) in environments and provide useful clues to tune the bioremediation of chromium-contaminated environments. Graphical abstract: Unlabelled Image Highlights: A. hydrophila ATCC 7966 had an excellent Cr(VI) resistance and reduction ability. Extracellular and intracellular pathways were involved in the Cr(VI) bioreduction. Medium composition affected the formation of Cr(VI) reduction products. Organo-Cr(III) complexes were the main Cr(VI) reduction products by Aeromonas .